Conservative Management of Prasramsini Yonivyapad - A Case Report - Walia, Pragati; Dhiman, Kamini (International Research Journal of Ayurveda & Yoga, 2021)
Uterine prolapse is a significant health concern affecting 2-20% of the women of reproductive age group. Laxity of vaginal canal & uterine descent is one of the conditions commonly seen as a complication of prolonged labor or patients having history of vaginal deliveries at home. Prasramsini yonivyapad mentioned by Acharya Sushruta, correlates with first degree Uterine Prolapse. This condition affects women mentally, socially and physically impairing their quality of life. A case was taken for study with symptoms of feeling of something coming out per vagina, increased frequency of micturition, stress incontinence. As Prasramsini is a Pittaja yonivyapad and Vata is the main dosha involved in all yonivyapad, the drugs selected for the study were mainly having the properties of vata and pitta doshahara, balya and agnivardhaka. Hence an attempt was made to treat Prasramsini yonivyapad and there was a marked improvement in symptoms. The basic treatment principles of both Ayurveda and contemporary science remains same but contemporary science has given more stress upon surgical management When the degree of prolapse is mild then the conservative line of treatment seems to be more beneficial.